2016
DOI: 10.1007/s10654-016-0167-1
|View full text |Cite
|
Sign up to set email alerts
|

Oral glucocorticoid therapy and all-cause and cause-specific mortality in patients with rheumatoid arthritis: a retrospective cohort study

Abstract: Previous studies of glucocorticoid (GC) therapy and mortality have had inconsistent results and have not considered possible perimortal bias—a type of protopathic bias where illness in the latter stages of life influences GC exposure, and might affect the observed relationship between GC use and death. This study aimed to investigate all-cause and cause-specific mortality in association with GC therapy in patients with rheumatoid arthritis (RA), and explore possible perimortal bias. A retrospective cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 29 publications
3
39
1
2
Order By: Relevance
“…The 2013 EULAR update on treatment recommendations of RA recommends addition of low-dose glucocorticoids as part of the initial treatment strategy for up to 6 months and tapering as soon as clinically feasible [40]. Positive dose-response association has been found between glucocorticoid use and CV mortality in RA [41]. However, our prior studies in this cohort showed that cumulative glucocorticoid dose, at least in the first year of RA diagnosis, has not changed significantly over time [36], suggesting no increase in adverse impact of glucocorticoid burden on CV mortality in more recent years vs. previously.…”
Section: Discussionmentioning
confidence: 99%
“…The 2013 EULAR update on treatment recommendations of RA recommends addition of low-dose glucocorticoids as part of the initial treatment strategy for up to 6 months and tapering as soon as clinically feasible [40]. Positive dose-response association has been found between glucocorticoid use and CV mortality in RA [41]. However, our prior studies in this cohort showed that cumulative glucocorticoid dose, at least in the first year of RA diagnosis, has not changed significantly over time [36], suggesting no increase in adverse impact of glucocorticoid burden on CV mortality in more recent years vs. previously.…”
Section: Discussionmentioning
confidence: 99%
“…We predefined several time-variant glucocorticoid exposure variables (Supplemental Figure 2, Appendix 1): 1) binary variable for current use (e.g., whether the patient received glucocorticoids at a given time point or not); 2) current daily dose per 5 mg/d (zero when medication was not prescribed), considered as continuous and categorical (nonuse, > 0.0-4.9 mg, 5.0-14.9 mg, 15.0-24.9 mg, ≥ 25.0 mg/d) variables; 3) cumulative dose since 1 year before follow-up start per 1000 mg, calculated by summing the total dose prescribed up to that point and dividing it by 1000 (this was also considered as continuous and categorical [nonuse, > 0-959 mg, 960-3054 mg, 3055-7299 mg, ≥ 7300 mg, cutoffs as defined by Movahedi and colleagues 19 ] variables); and 4) cumulative dose 1 year before the end of follow-up, calculated by summing the total dose from 1 year before the end of follow-up or the whole study period if the duration of follow-up was less than 1 year. To create these variables, we determined the start and end of each medication exposure period and split patient follow-up on the dates on which the dose changed (Appendix 2).…”
Section: Oral Glucocorticoid Exposurementioning
confidence: 99%
“…To our knowledge, there are no studies in RTR which investigated the association of urinary cortisol metabolism and mortality long‐term after kidney transplantation. However, there are studies in other populations, such as patients with rheumatoid arthritis, pituitary adenoma, acromegaly, and alcoholic hepatitis, showing that treatment with higher doses of corticosteroids is associated with an increased risk of mortality.…”
Section: Discussionmentioning
confidence: 99%